Survival of FimH-expressing enterobacteria in macrophages relies on glycolipid traffic. - Baorto, D; Gao, Z; Malaviya, R; Dustin, M; van der Merwe, A; Lublin, D; Abraham, SN (1997)
Strains of Escherichia coli persist within the human gut as normal commensals, but are frequent pathogens and can cause recurrent infection. Here we show that, in contrast to E. coli subjected to opsonic interactions stimulated by the host's immune response, E. coli that bind to the macrophage surface exclusively through the bacterial lectin FimH can survive inside the cell following phagocytosis. This viability is largely due to the attenuation of intracellular free-radical release and of phagosome acidification during FimH-mediated internalization, both of which are triggered by antibody-mediated internalization. This different processing of non-opsonized bacteria is supported by morphological evidence of tight-fitting phagosomes compared with looser, antibody-mediated phagosomes. We propose that non-opsonized FimH-expressing E. coli co-opt internalization of lipid-rich microdomains following binding to the FimH receptor, the glycosylphosphatidylinositol-linked protein CD48, because (1) the sterol-binding agents filipin, nystatin and methyl beta-cyclodextrin specifically block FimH-mediated internalization; (2) CD48 and the protein caveolin both accumulate on macrophage membranes surrounding bacteria; and (3) antibodies against CD48 inhibit FimH-mediated internalization. Our findings bring the traditionally extracellular E. coli into the realm of opportunistic intracellular parasitism and suggest how opportunistic infections with FimH-expressing enterobacteria could occur in a setting deprived of opsonizing antibodies.